Desain Vaksin Berbasis Epitop dengan Pendekatan Bioinformatika untuk Menekan Glikoprotein Spike SARS-CoV-2 - M Afrizal Firmansyah; Aris Susilo; Septina D Haryanti; Rina Herowati (Fakultas Farmasi Universitas Setia Budi, 2021)
Vaccination is one of the main prevention of the spread of Covid-19. Technological engineering based on virus attenuation has been applied in vaccine development. This study aims to obtain an epitope-based vaccine design with low risk of allergic reactions, safe, and inexpensive. The design of the vaccine was conducted by the collection of SARS-CoV-2 sequence data, phylogenetic analysis, prediction of protein antigenicity, and identification of CD 8+ T cell epitopes. Furthermore, epitope conservation and immunogenicity prediction, as well as molecular docking analysis were carried out to see the interaction between epitopes and alleles. The next step was B cell epitope prediction, population coverage prediction, construction and visualization of vaccine design, structural analysis and validation, interaction analysis between vaccines with TLR 3 and TLR 4, and evaluation of vaccine design immunogenicity. All stages were carried out using the appropriate webserver. The designed vaccine had an antigenicity of 0.5134, not toxic, and not allergenic. The physicochemical parameters met the requirements except for the molecular weight which was less than 40 KDa. The designed vaccine was predicted to have a population coverage of 95.14% for the Indonesian population. The results of the immunogenicity prediction of the vaccine design showed an increase of IgM and IgG until day 35.